Students' Perception Towards the Implementation of Team Based Project in Intermediate Reading Class at English Department UNP - Tri Wahyudi; M. Zaim (Journal of English Language Teaching, 2022)
This study aims to describe students’ perceptions towards the implementation of Team Based Project in intermediate reading class at English Department UNP and the benefits of Team Based Project. This is a descriptive quantitative study. The sample for this research was 59 students of English Department in Universitas Negeri Padang who have taken Intermediate reading course. The data collection technique used in this research was a questionnaire and interview. The results of this study indicated that the majority of Intermediate reading students in English Department had a positive perception of the implementation of Team Based Project. The students agree that the use of Team Based Project motivates students to learn and also improves students’ skills. Based on the finding, it can be concluded that the students in Intermediate reading class have positive perception toward the implementation of Team Based Project and also the students can get several benefits from the implementation of Team Based Project.